Memaknai Bhineka Tunggal Ika dalam Perspektif Kristiani - Marianto, Yohanes Robini (Jurnal Orientasi Baru, 2010)
This paper is an attempt to explore understanding and meaning of the realities of human life traits such unity in diversity from Christian perspectives. According to the author, talks about the pluralism that is based on the depth of God should be in touch with the mystery of God or the mystery of faith in the Triune God. The triune God is an example of how Christians should be open in respect for differences and uniqueness of all parties. If God does not forbid the difference in himself, it is fatal and the contradiction that His creation did not appreciate each other in the difference.